Highly Regio- and Stereoselective Synthesis of Tetracyclic Indolenoisoxazolidines via Intramolecular 1,3-Dipolar Nitrone Cycloadditions - Bakthadoss, Manickam; Sivakumar, Govindan; Sharada, Duddu S. (Synthesis, 2013)
A facile method for the simple synthesis of tetracyclic indoloisoxazolidine frameworks from Baylis–Hillman derivatives through formation of nitrones in situ followed by an intramolecular [3+2]-dipolar cycloaddition reaction sequence is described. High regio- and stereoselectivity, excellent yields, together with the creation of two rings and three contiguous stereogenic centers including one all carbon quaternary center, are the salient features of the present method.
Keywords: fused-ring systems; indoles; 1,3-dipolar cycloaddition; stereoselectivity; regioselectivity